Romanian Roma: An Institutional Ethnography of Labour Market Exclusion - Breimo, Janne Paulsen (Social Inclusion, 2016)
Roma individuals are struggling to access the formal labour market in Romania. Previous research occupied with this issue has traditionally been dominated by quantitative studies of socio-economic indicators that cling to the characteristics of the ethnic group. The study presented here, however, uses institutional ethnography as a method of social inquiry to demonstrate that this issue needs to be studied from a bottom-up perspective. The article illustrates that there are factors connected to how the system of occupational integration operates that must be taken into consideration in order to explain the difficulties Roma individuals face when trying to enter the labour market in Romania. We argue that these structural barriers create and reinforce processes of minoritising that increase marginalization and discrimination and thereby hinder work inclusion for Roma individuals.